Increasing Branding Awareness of Alfath Mart as UMKM in Medan City Through Video Advertising Creative Media - Fuad Erdansyah; Mukhlis Mukhlis; Khaerul Saleh (Gondang: Jurnal Seni dan Budaya, 2023)
This research was conducted to produce an advertising video concept that is attractive, creative and economically valuable. This research is based on the desire to produce a creative and innovative product that can be applied as a promotional medium that can be useful for building the economic activities of the Medan City UMKM group. This research aims to produce a method for producing video advertisements for UMKM products as branding media for Medan City UMKM. The method used in this research is a qualitative approach. The process of searching for data and information was carried out using in-depth interviews with videography experts, Medan city UMKM, and Medan city UMKM product consumers as informants. Apart from that, literacy studies were also carried out such as journals, newspapers, magazines and other materials containing information about branding and UMKM. The research results concluded that in introducing and promoting a product or brand, the use of promotional videos could be an option. Publication of Medan City UMKM products through advertising video media can be done as an effort to increase brand awareness. Promotional videos are able to convey messages well so that they get the desired response.